Pengaruh waktu penyimpanan sediaan larutan oral nutraceutical dari ekstrak etanol bunga delima merah (punica granatum l.) terhadap oksidasi - Marzuki, Ismail; , drg. Mahmud Kholifa, MDSc (2017)
Oral health is one of the most important thing in human health. One of the solutions to maintenance oral health is by using oral nutraceutical. Oral nutraceutical could be made from natural source like pomegranate fllower that containing advantages substances. Oral nutraceutical as natural product usually has short shelf life that could be affected by oxidation process during storage. The aim of this study is to figure out the effect of storage time on oral nutraceutical oxidation from pomegranate (Punica granatum L) flower ethanolic extract. The type of this study was purely experimental laboratory. This study was done by divided oral nutraceutical sampels into five treatment groups, i.e. without saving treatment group, 168 hours, 336 hours, 504 hours, and 672 hours saving treatment groups. Each treatment group was measured by using spectrophotometer UV-Vis to evaluate the color change caused by oxidation. The results showed that storage time had an effect on oral nutraceutical oxidation. One way Anova test results showed the value p=0.000 (p<0.005) that means there was significant difference in the treatment groups. Post hoc LSD test showed that there was no significant difference among without saving treatment group, 168 hours, 336 hours, and 504 hours treatment group, but had significant difference compared to 672 hours treatment group. Conclusion of this study was oral nutraceutical from pomegranate (Punica grantum L.) flower ethanolic extract had no significant effect on oxidation until 504 hours saving treatment.